The impact and effects of trauma resulting from excommunication - Kubeka, Mpiyakhe J. (HTS teologiese studies, 2010)
This article will attempt to critically analyse various aspects of the state of trauma. It will analyse the impact, consequences and effects of trauma resultant from excommunication of clergy and how the practice has been handed down through the ages. The ultimate aim of the authors is an understanding of how excommunication evolved throughout the ages and the nature of its impact on the victims or survivors thereof. The author’s own first-hand encounter prompted him to research this subject. It is imperative to look at the scientific application of the ritual as it affects all the stakeholders and participants, active or passive.An overview of various biblical eras will be given, including the Old Testament prophets, Christ’s own views as well as the period of St Paul in the New Testament.